A Case for the Revision of Power Engineering Syllabi at Kenyan Universities - Odero, Nicodemus Abungu; Munda, Josiah; Akumu, Aloys (My University, 2005)
This paper presents a summary of the current status of Elec-trical Power Engineering Education at Kenyan universities,followed by a summary of the situation on the same at universities world-wide. Against a backdrop of expected changes in the Kenyan power industry, the paper discusses the industry expectations of a power systems graduate cur-rently and in the future, making a case for the revision of the current power engineering syllabi, concluding with recommendations and strategies for making the required changes.
Keywords: Power engineering education; Electric power systems; Syllabi; Status report